Zero-Valent Iron and Sand Filtration Reduces Levels of Cyclospora cayetanensis Surrogates, Eimeria tenella and Eimeria acervulina, in Water - Alan Gutierrez; Matthew S. Tucker; Christina Yeager; Valsin Fournet; Mark C. Jenkins; Jitender P. Dubey; Kalmia E. Kniel; Benjamin M. Rosenthal; Manan Sharma (Microorganisms)
Recurring outbreaks of cyclosporiasis linked to fresh produce demonstrate the need to develop interventions to reduce C. cayetanensis in irrigation water. C. cayetanensis is resistant to commonly used irrigation water treatments, such as chemical sanitizers, making removal of oocysts by filtration the most suitable intervention. This study evaluated the reduction of Eimeria tenella and E. acervulina, as surrogates for C. cayetanensis, in water using filters packed with sand alone or mixtures of sand and zero-valent iron (ZVI). Water inoculated with Eimeria spp. oocysts was filtered through laboratory-scale (PVC column) and field-scale (swimming pool filter) filters packed with either 100% sand or 50% ZVI/50% sand (v/v). Filtered and backflush water was examined microscopically for oocysts. Laboratory-scale filters with 50% ZVI significantly (p < 0.05) reduced 99.9% of E. tenella oocysts compared to 55.3% with filters containing 100% sand. At the field-scale level, 50% ZVI filters significantly (p < 0.05) reduced 70.5% of E. acervulina oocysts compared to 54.5% by 100% sand filters. Filters were backflushed to examine the recovery of these parasites during routine filter-media cleaning procedures. Backflush recovery of oocysts ranged from 4.42–16.7%. The addition of ZVI significantly improved the reduction of Eimeria spp. oocysts at both filter scales. and should be further investigated as a potential irrigation water intervention to reduce C. cayetanensis.